Pelatihan Hidroponik Untuk Pemberdayaan Warga Desa Kalipecabean, Kecamatan Candi, Kabupaten Sidoarjo Yang Bernilai Ekonomis - Isrianto, Pramita Laksitarahmi; Marmi, Marmi; Kristianto, Sonny; Wilujeng, Sukian; Sunaryo, Sunaryo; Chamidah, Dina (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2023)
Hydroponics is an agricultural technique that uses water as a substitute for soil as a medium. Planting can improve one's character, especially the character of concern for the environment. aims to provide training on hydroponic plants to introduce hydroponic plants, beautify the environment so it looks beautiful, and support economic needs. The method used in community service activities is through offline and online methods. The offline method implementation activities are to provide training, practice and mentoring using lecture methods, question-answer discussions and demonstrations. As for the online method for consultation and evaluation of participants through the WhatsApp Group. Apart from that, assistance was provided to PKK women from Kalipecabean Sidoarjo village so they could beautify the environment, produce healthy hydroponic plants and open independent businesses to improve the welfare of residents and support the Surabaya Green and Clean program. This training can add to the participant's insight about hydroponics and know the correct hydroponic farming technology. The enthusiasm of the participants was very high and showed very good results and they hope that there will be a continuation of the next training program in Kalipecabean Village, Candi District, Sidoarjo.